MODELING OF QUEUES AT 3 KG LPG FILLING AND TRANSPORTATION STATIONS (SPPBE) WITH OPTIMIZATION OF PROMOTIONAL SERVICE STATIONS - Zabrina, Siti; Nasyifa, Hesti; Febryand, Calvin (International Journal of Global Operations Research, 2025)
Queues are a common problem that often arises from an imbalance between the arrival rate and the service capacity or facilities. Queues occur because customers (users) arrive at a service facility when the available service capacity is insufficient to handle the incoming demand. Queues often occur in the Single Channel - Single Phase queue system, which is observed at SPPBE (Filling and Transportation Stations for Bulk LPG). In the Single Channel - Multi Phase queue structure, queues also occur due to the accumulation of waiting time required for each service stage. Therefore, this research aims to explain the model and analyze the queue system that occurs at SPPBE, provide an explanation of the analysis results of the Single Channel - Single Phase queue model for two service locations, and use the Kolmogorov-Smirnov method for data conformity testing. The SPSS program was used to analyze the Single Channel - Single Phase queue model for two service locations and to use the Multi Channel - Multi Phase queue model for the two service locations.